“Lone Soldiers” in the Israeli Military—A Research Note on the Conceptualization of Foreign Fighters - Schmutz, Timrah (Terrorism and political violence, 2022)
This research note contributes to the growing body of knowledge on foreign fighters in international affairs. While most scholars in the field derive their understanding of the phenomenon from highly publicized cases of Western Muslims fighting alongside Jihadi groups in the Middle East, this article brings a new case study into the arena: Jewish foreign nationals who voluntarily enlist in the Israeli military, also known as lone soldiers. After a presentation of this to date unexplored case (i.a. through nineteen semi-structured interviews), the article delves into the conceptual realm, discussing whether Israel’s lone soldiers can be analyzed within the foreign-fighter framework in the first place. Based on the empirical findings and an interdisciplinary literature review on foreign fighters the article argues that lone soldiers do constitute a relevant case study. This research note further suggests that much of the controversy on conceptual matters could be avoided by understanding the phenomenon as an action (i.e., foreign fighting) rather than an actor (i.e., foreign fighter). Further research is warranted to support these findings.